Research on Soil Erosion Intensity and Spatial Distribution Characteristics in Zhaoyang District of Zhaotong City Based on RS and GIS - Pan, Maohua; Wang, Ruei-Yuan; Lu, Bing-Yuh (International Journal of Environment, Agriculture and Biotechnology, 2023)
This article takes Zhaoyang District, Zhaotong City, Yunnan Province, as the study area. By obtaining basic data such as rainfall, soil texture data, digital elevation, land use, and remote sensing images, the RUSLE model is used to estimate the soil erosion modulus in Zhaoyang. Based on this, the soil erosion classification and soil erosion of different land use types in the study area are analyzed. The results have shown that the soil erosion intensity in Zhaoyang, shows a pattern of increasing from southeast to northwest. Most of the land is subject to slight erosion, followed by mild and moderate erosion. The strongly eroded soil is concentrated in the northwest and is greatly affected by altitude and slope factors. The proportion of soil micro erosion is 64.4%, the proportion of mild erosion area is 17.58%, the proportion of moderate erosion area is 11.99%, and the proportion of strong erosion, extremely strong erosion, and severe erosion area are 3.74%, 1.55%, and 0.74%, respectively. The erosion amount of land use types such as construction land and water bodies is very small, and overall it is at a micro erosion level. Shrubs, forests, and grasslands are the main sources of regional erosion, and the soil erosion intensity of cultivated land is high.